Commercial Law on the Beach: Shore Whaling Litigation in Early Colonial New Zealand: Macfarlane v Crummer (1845) - Anderson, Stuart (Victoria University of Wellington Law Review, 2010)
During the 1844 whaling season John Sangster Macfarlane supplied provisions to a new shore whaling station at Wairoa which, unusually, had been established by whaling hands themselves. In probable breach of contract their chief headsman sold some of the station’s produce to a passing trader, Thomas Crummer, whom Macfarlane then sued for conversion. The litigation in the Supreme Court at Wellington in 1845 established a baseline rule for the benefit of mercantile outfitters of whaling stations. The special jury of merchants heard evidence from other merchants about local custom and probably based their decision upon that, reaching a conclusion not otherwise open to them under the general rules of common law. But they tempered their verdict to acknowledge that the custom deeming Macfarlane to own the station brought responsibility too. The episode illustrates one way of adapting common law to local circumstance in a young colony, and is congruent with an earlier shore whaling case, Harris v Fitzherbert, where custom played a similar role.